1978
DOI: 10.3758/bf03214300
|View full text |Cite
|
Sign up to set email alerts
|

The judgment of distance on a plane surface

Abstract: A test was made of the scalability of interval-ordering judgments of distance along the median path of a plane horizontal surface. Scales were derived from different subsets of judgments. It was found that scale values were related to distance by a power function with marked individual differences in exponent, but that different subsets of judgment yielded the same mean exponent. This finding was taken as positive evidence of scalability. The individual differences in judgment were shown to be reliable over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…001. This result is consistent with previous research demonstrating a compression of perceived space for distances greater than about 3 m (e.g., Cook, 1978;Norman, Todd, Perotti, & Tittle, 1996). Overall, the participants primed with the elderly stereotype judged the distances to be longer than the control participants did (control: M = 8.01 m; stereotype: M = 9.96 m), thus accurately estimating the smaller distances (between 4 and 8 m) and overestimating the larger ones.…”
Section: Resultssupporting
confidence: 90%
“…001. This result is consistent with previous research demonstrating a compression of perceived space for distances greater than about 3 m (e.g., Cook, 1978;Norman, Todd, Perotti, & Tittle, 1996). Overall, the participants primed with the elderly stereotype judged the distances to be longer than the control participants did (control: M = 8.01 m; stereotype: M = 9.96 m), thus accurately estimating the smaller distances (between 4 and 8 m) and overestimating the larger ones.…”
Section: Resultssupporting
confidence: 90%
“…The results of these two studies suggest that apparent intervals of fixed size increase with viewing distance. With the method of equal-appearing intervals, on the other hand, Cook (1978) indicated that, at distances of2 m or less, apparent distance is proportional to objective distance. Thus, distance estimates seem accurate as a whole, although they may depend on many factors.…”
Section: Definitions and A Review Of Close Objectsmentioning
confidence: 99%
“…A number of studies (Baird & Wagner, 1982;Cook, 1978;Da Silva, 1983, 1985Galanter & Galanter, 1973;Kuroda, 1971;Ohno, 1972;M. Teghtsoonian & R. Teghtsoonian, 1969;R.…”
Section: Scales For Perceived Distancementioning
confidence: 99%